Optimizing Sparse Linear Algebra for Large-Scale Graph Analytics - Buono, Daniele; Gunnels, John A.; Xinyu Que; Checconi, Fabio; Petrini, Fabrizio; Tai-Ching Tuan; Long, Chris (Computer (Long Beach, Calif.), 2015)
Emerging data-intensive applications attempt to process and provide insight into vast amounts of online data. A new class of linear algebra algorithms can efficiently execute sparse matrix-matrix and matrix-vector multiplications on large-scale, shared memory multiprocessor systems, enabling analysts to more easily discern meaningful data relationships, such as those in social networks.